2017
DOI: 10.4269/ajtmh.17-0093
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Levels and the Risk of Malaria in Papua New Guinean Infants: A Nested Cohort Study

Abstract: Studies are available that assess the risk of malaria in accordance to the body's iron store and the systematic iron supplementation of preschool children. However, only a few studies evaluated the temporal association between hemoglobin and malaria and their results are opposing. A total of 1,650 3-month-old Papua New Guinean infants were enrolled in this study and followed-up for 12 months. The risk of malaria was assessed in all children every 3 months and with each episode of fever. The incidence of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…nutrient supplementation) and exposure to infectious disease (i.e. fever, malaria, intestinal parasites) (Mueller et al 2017;Paganini and Zimmermann 2017). Secondly, there are underlying causes at the household/family level, such as access to water and sanitation, availability of health services, childcare practice (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…nutrient supplementation) and exposure to infectious disease (i.e. fever, malaria, intestinal parasites) (Mueller et al 2017;Paganini and Zimmermann 2017). Secondly, there are underlying causes at the household/family level, such as access to water and sanitation, availability of health services, childcare practice (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations from 2 previous studies have been reported. A recent longitudinal study in Papua New Guinean infants aged 3 months and followed for 1 year reported a nonsignificant association between lower hemoglobin concentrations and subsequent malaria infection [19]. Ghosh et al made a similar observation in Indian children [20].…”
Section: Discussionmentioning
confidence: 97%
“…In mouse models, hepcidin has been shown to play a role in preventing superinfection by depriving the Plasmodium liver stage of iron [16], but studies in children have reported mixed findings [17, 18]. Two previous studies have reported that hemoglobin concentrations do not influence malaria risk [19, 20], while in vitro culture indicates otherwise [21]. There are no specific reports of the influence of sTfR and TSAT on malaria in humans.…”
mentioning
confidence: 99%
“…This clearly explains that individuals who carried the variant GG genotype confer a protective risk effect against P. vivax infection by 0.5-fold, as observed in the present study. However, a recent study reported that infants with lower hemoglobin levels are not protected against malaria infection in a Papua New Guinean population [ 30 ]. Since the present study only involved adults and the hemoglobin level of the subjects is not assessed, further studies that investigate the risk of malaria in relationship with age differences and hemoglobin levels would be important for a better understanding of this complex interaction.…”
Section: Discussionmentioning
confidence: 99%